De facto informality? Rethinking the experience of women in the formally regulated workplace. (3rd April 2018) - Heap, Lisa; Barnes, Tom; Weller, Sally
ABSTRACT: This paper argues that characteristics usually associated with informal work, including a lack of protection under the law, diminished voice and agency, are routinely experienced by women in formally regulated workplaces in Australia. Despite a raft of formal legislation to prohibit gender-based discrimination, outlaw gendered violence and promote workplace health and safety, an experience of de facto informality undermines women's agency to address everyday discrimination and gendered violence at work. This reality is attributed to the patriarchal social norms that dominate in many workplaces, which create challenges for the enforcement of legal regulation and which lead women to tolerate unsatisfactory conditions despite avenues for formal legal protection and compensation. The lens of de facto informality, we argue, highlights the gap between the legislative intent and the lived experience of working women, the limitations of regulation and the need for collective action to address gender inequality and improve women's capacity to exercise their agency at work.